Sifat Fisik Tanah Pada Lahan Bawang Merah Di Kecamatan Gondang Nganjuk dan Kecamatan Kedungadem Bojonegoro - Nugroho, Muhammad Vedo Prasetyo; Arifin, Moch.; Widjajani, Bakti Wisnu (Jurnal Solum, 2023)
Soil physical properties are those soil properties that affect plant growth and production, determining root penetration into the soil, soil water-holding capacity, drainage, soil aeration, and soil nutrient availability. Shallots prefer fertile soil, loose, and rich in organic matter. Loose and fertile soil produces large tubers. This research was conducted to determine and study the physical properties of the soil on shallots in Kecamatan Gondang, Nganjuk and Kecamatan Kedungadem, Bojonegoro. Undisturbed and disturbed soil samples were taken at depths of 0-20 cm and 20-40 cm. Determination of the sampling point using the Purposive Random Sampling method based on the type of soil and land use as well as surveying the location of observations. The selected soil types are Vertisols and Inceptisols. Each soil type is represented by 3 sampling points. The results showed that the physical properties of the various shallot fields studied had a soil texture dominated by clay and silt with a silty clay texture class, moderate bulk density, good soil porosity, soil permeability has various classifications from slow to fast, very stable. aggregate stability, and has low C-Organic material. Several parameters of the physical properties of the soil are suitable for growing shallots. However, the C-Organic content is still in the low category and it cannot meet the need for organic matter for shallot cultivation.Key words : soil physical, shallot, Vertisols, Inceptisols